2018
DOI: 10.1016/j.jphs.2018.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of pramipexole transdermal patch in the MPTP-induced mouse model of Parkinson's disease

Abstract: Parkinson's disease (PD) is characterized by the selective death of dopaminergic neurons. To avoid inconvenience of frequent administration caused by short half life and recurrence of symptoms such as tremor and bradykinesia incurred by drug elimination, a novel long-acting pramipexole transdermal patch has been made. In the present study, we evaluated the neuroprotective effects and underlying mechanisms of pramipexole patch (PPX patch) in a subacute PD mouse model induced by 1-Methyl-4-phenyl-1,2,3,6-tetrahy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Mechanistically, PPX promoted a reduction in mitochondrial ROS, which could be one of the possible explanations for these findings. Many studies support the anti-oxidative nature of PPX (Sayeed et al, 2006; Wang et al, 2018). Thus, it can be concluded that the anti-oxidative property of PPX could promote recovery in mitochondrial respiration after ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, PPX promoted a reduction in mitochondrial ROS, which could be one of the possible explanations for these findings. Many studies support the anti-oxidative nature of PPX (Sayeed et al, 2006; Wang et al, 2018). Thus, it can be concluded that the anti-oxidative property of PPX could promote recovery in mitochondrial respiration after ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Post-treatment with PPX reduced the release of cyt-c by attenuating the mitochondrial damage. Previous studies have demonstrated that PPX inhibits cyt-c leakage in different cell lines and in vivo ( Shin et al, 2007 ; Wang et al, 2018 ). Based on the present results, we can conclude that PPX treatment protects mitochondria by multiple pathways in TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have demonstrated the relationship between PPX and Nrf2 following brain injury. Recently, Wang et al (2018) reported that PPX administration increased the expression of Nrf2 in 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced Parkinson's disease. However, the molecular mechanism underlying the effects of PPX in TBI is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…it inhibits mitochondrial permeability transition pores, when given in nanomolar concentrations, by binding to the inner side of the mitochondrial membrane [43]. Mitochondrial mechanisms have been suggested to underlie antioxidant, antiapoptotic, neuroprotective efficiency of pramipexole which is visible already after its low doses [44,45]. It is currently unknown whether such non-dopaminergic mechanism indeed contributes also to the inhibitory influence of pramipexole on harmaline effects described in the present study and earlier [5] and to the tremorolytic effects of this drug in ET [21].…”
Section: Discussionmentioning
confidence: 99%